Laboratory investigations of wave attenuation by simulated vegetation of varying densities. Issue 2 (4th May 2019) - John, Beena Mary; Shirlal, Kiran G.; Rao, Subba
Abstract: Coastal communities across the world are facing the need to adapt to rising sea levels, an increase in the frequency of natural hazards like storm surges, cyclones, tsunamis, and an increase in beach erosion. This present-day scenario calls for a sustainable, environment-friendly, and cost efficient solution for coastal protection. Under these circumstances, the role of vegetation in providing ecosystem services to coastal populations is becoming increasingly prominent. This work presents the results of an experimental study carried out with simulated rigid submerged and emergent vegetation meadows of varying plant densities in a wave flume 50 m long, 0.71 m wide and 1.1 m deep. The material used for modeling the vegetation is nylon. The tests are carried out with regular waves for water depths of 0.40 and 0.45 m, and wave periods 1.4–2 s at an interval of 0.2 s. Five different wave heights ranging from 0.08 to 0.16 m at an interval of 0.02 m are generated. Measurements of wave heights at different locations indicate an exponential decay in wave height along the vegetation meadow which leads to wave attenuation and confirms that vegetation can be a viable option for coastal protection.